Predictive biomarkers for immune checkpoint blockade and opportunities for combination therapies - Shen, Hongxing (Genes Dis, 2019)
Immune checkpoint blockade therapies (ICBs) are a prominent breakthrough in cancer immunotherapy in recent years (named the 2013 “Breakthrough of the Year” by the Science magazine). Thus far, FDA-approved ICBs primarily target immune checkpoints CTLA-4, PD-1, and PD-L1. Notwithstanding their impressive long-term therapeutic benefits, their efficacy is limited to a small subset of cancer patients. In addition, ICBs induce inadvertent immune-related adverse events (irAEs) and can be costly for long-term use. To overcome these limitations, two strategies are actively being pursued: identification of predictive biomarkers for clinical response to ICBs and multi-pronged combination therapies. Biomarkers will allow clinicians to practice a precision medicine approach in ICBs (biomarker-based patient selection) such as treating triple-negative breast cancer patients that exhibit PD-L1 staining of tumor-infiltrating immune cells in ≥1% of the tumor area with nanoparticle albumin-bound (nab)–paclitaxel plus anti-PD-L1 and treating patients of MSI-H or MMR deficient unresectable or metastatic solid tumors with pembrolizumab (anti-PD-1). Importantly, the insights gained from these biomarker studies can guide rational combinatorial strategies such as CDK4/6 inhibitor/fractionated radiotherapy/HDACi in conjunction with ICBs to maximize therapeutic benefits. Further, with the rapid technological advents (e.g., ATCT-Seq), we predict more reliable biomarkers will be identified, which in turn will inspire more promising combination therapies.